IS IT POSSIBLE TO IMPROVE THE ADHERENCE TO TREATMENT OF HYPERTENSION AND DYSLIPIDEMIA IN PATIENTS WITHOUT CLINICAL MANIFESTATIONS OF ATHEROSCLEROSIS? - A. А. Sarycheva; D. V. Nebieridze; T. V. Kamyshova (Рациональная фармакотерапия в кардиологии)
The search for effective ways to improve adherence to medication in patients with hypertension at high risk is critical in reducing morbidity and mortality from cardiovascular diseases.Aim. To assess the possibility of improving adherence to therapy in high-risk hypertensive patients with dyslipidemia by means of electronic version of the SCORE scale in primary care.Material and methods. 300 hypertensive patients with dyslipidemia aged 40 to 65 years without clinical manifestations of atherosclerosis visiting primary care doctor  (departmental clinic of Moscow) were examined. The study included only patients (n=150) with high cardiovascular risk and target organ damages (microalbuminuria, left ventricular hypertrophy, subclinical carotid atherosclerosis). The patients were randomized into two groups – main (n=76) and control (n=74). All patients were prescribed antihypertensive and lipid-lowering therapy, recommendations for a healthy lifestyle. In the main group, the positive dynamics of risk was demonstrated with the electronic version of the SCORE scale in the case of achieving target levels of blood pressure (BP) and total cholesterol, smoking cessation and weight loss. No such demonstration was done in the reference group.  The duration of study was 12 months. In the groups, evaluation of the achievements of target BP values and lipid variables, risk factors correction, dynamics of SCORE risk and adherence to therapy was done.  Adherence to treatment was assessed by Morisky-Green scale.Results. By the end of the study, the average Morisky-Green score in the main group was 2.14 vs 1.27 in the control group (p<0.001). In the main group, adherence to antihypertensive therapy persisted for 8.8 months, to statin therapy – 6.74 months; the same characteristics in the control group were 5.73 and 3.6 months, respectively (p<0.001). Achievement of target levels of BP and total cholesterol in the main group  amounted to 55.3% and 35.5% of patients, respectively, in the control group  – 18.9% and 10.8%, respectively (p<0.001). The SCORE risk value was significantly lower in the main group than this in control group (4.09 vs 5.25, respectively).Conclusion. Demonstration of electronic version of SCORE scale for high-risk hypertensive patients with dyslipidemia allows increasing the patient's adherence to treatment. This leads to the increase in the effectiveness of therapy, better control of BP and lipid parameters, correction of other modifiable risk factors and as a result to reducing overall cardiovascular risk.